Lithium Borate Ionic Liquids as Single-Component Electrolytes for Batteries - Guzmán González, Gregorio (2023)
Current electrolytes for lithium batteries are usually composed of at least two chemical compounds, an organic solvent such as a cyclic carbonate and a lithium salt such as LiPF6. Here, the concept of using a single-component electrolyte is demonstrated in lithium batteries based on new lithium borate ionic liquids at room temperature. The design concept of this class of lithium ionic liquids (LiILs) is based on an asymmetrically substituted central tetracoordinate boron atom with oligoethylene glycol groups, fluorinated electron-attracting groups, and one alkane group. The optimized borate-Li+ LiILs show a high ionic conductivity value of >10−4 S cm−1 at 25 °C, high lithium transference numbers ((Formula presented.) = 0.4 – 0.5) and electrochemical stability (>4 V). Some of the LiILs present high compatibility with lithium-metal electrodes showing stable polarization profiles in platting/stripping tests. The selected LiIL is investigated as single-component electrolytes in lithium-metal battery cells showing discharge capacity values in Li0/LiIL/lithium–iron phosphate and Li0/LiIL/lithium titanate cells of 124 and 75 mAh g−1, respectively, at a C-rate of 0.2 C and 65 °C with low-capacity loss.